2021
DOI: 10.24874/ti.970.09.20.11
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Dry Sliding Wear Performance and Corrosion Resistance of 13Cr5Ni2Mo Supermartensitic Stainless Steel

Abstract: This work aimed to study the microstructure, wear and corrosion resistance of supermartensitic stainless steel (SMSS). Heat treatment applied to samples consists of quenching after austenitization at elevated temperature (1250 °C) followed by a double tempering at 650 °C. Conventional mechanical properties, scanning electron microscopy (SEM/EDS) analysis and X-ray diffraction methods (XRD) are used to analyze the microstructure and to evaluate the wear mechanisms. The potentiodynamic polarisation and the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…By observing Figure 12(A), one can see that the worn surface morphology of unborided samples for low loads presents a relatively rough wear track with small holes, severe abrasive wear, and oxidative wear followed by soft third body abrasive whereas the adhesion phenomenon is observed for higher loads. These mechanisms have also been observed by Beliardouh et al [59]. For borided samples shown in Figure 12(B), a defined wear scar was produced, which increases with increasing applied loads.…”
Section: Resultssupporting
confidence: 82%
“…By observing Figure 12(A), one can see that the worn surface morphology of unborided samples for low loads presents a relatively rough wear track with small holes, severe abrasive wear, and oxidative wear followed by soft third body abrasive whereas the adhesion phenomenon is observed for higher loads. These mechanisms have also been observed by Beliardouh et al [59]. For borided samples shown in Figure 12(B), a defined wear scar was produced, which increases with increasing applied loads.…”
Section: Resultssupporting
confidence: 82%
“…They are characterized by their ability to combine high tensile, good wear, and chemical corrosion resistance against aggressive solution environments. All these properties are critical to overcoming the harsh surrounding environmental conditions that severely affect the quality of machines in the industry [4,5]. Consequently, Martensitic stainless steel alloys are used to construct seamless tubes in oil or gas industries, industrial knives, oil pipelines and pumps, or other parts of machines suitable for the petroleum or agriculture instrumental industries [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that increasing applied load enhances the worn volume loss of the investigated material according to the self-impedance of the studied material against plastic deformation. The heat treatment process could also produce better mechanical properties of the martensitic alloys that are recycled for industrial applications [5]. A further study has been carried out to determine the effect of tempering on the electrochemical corrosion properties of the Martensitic grade AISI4130, indicating that the heat treatment process leads to a decreased electrochemical corrosion current (IC) against 3.5% NaCl water saline solution.…”
Section: Introductionmentioning
confidence: 99%